Protein Lysine Acetylation in Ovarian Granulosa Cells Affects Metabolic Homeostasis and Clinical Presentations of Women With Polycystic Ovary Syndrome - Min, Zheying; Long, Xiaoyu; Zhao, Hongcui; Zhen, Xiumei; Li, Rong; Li, Mo; Fan, Yong; Yu, Yang; Zhao, Yue; Qiao, Jie (Frontiers in Cell and Developmental Biology, 2020)
Polycystic ovary syndrome (PCOS) is one of the most common reproductive endocrine disorders accompanied by the obvious metabolic abnormalities. Lower-quality oocytes and embryos are often found in PCOS women during assisted reproductive technology treatment. However, there is still unclear about the mechanism of ovarian metabolic disorders and the impact on oocyte maturation in PCOS. The aim of this study was to understand the potential effect of the posttranslational modification on ovarian metabolic homeostasis and oocyte development potential in women with PCOS. A quantitative analysis of acetylated proteomics in ovarian granulosa cells of PCOS and control groups was carried out by mass spectrometry. There was widespread lysine acetylation of proteins, of which 265 proteins had increased levels of acetylation and 68 proteins had decreased levels of acetylation in the PCOS group. Most notably, differentially acetylated proteins were significantly enriched in the metabolic pathways of glycolysis, fatty acid degradation, TCA cycle, tryptophan metabolism and branched-chain amino acids degradation. Acetyl-CoA acetyltransferase 1 (ACAT1) was an enzyme central to these metabolic pathways with increased acetylation level in PCOS group, and there was negative correlation of ACAT1 acetylation levels in PCOS granulosa cells with the oocyte quality and embryo development efficiency in the clinic. Lysine acetylation changes of key enzymes in PCOS granulosa cells might attenuate their activities and alter metabolic homeostasis of follicular microenvironment for oocyte maturation and embryo development.